Is There Endometriosis Effect on Economic Burden? - Sutrisno, MD, PhD, OG (REI) (Asian Journal of Health Research, 2023)
Endometriosis is a chronic inflammation with a specific characteristic being the appearance of endometrial-like tissue outside the uterus. Symptoms of endometriosis are usually non-specific and can be found to be similar to symptoms of other gynecological and even gastrointestinal disorders. The nature of the disease, enigmatic and needs more cost at every step, stimulate the economic burden in managing endometriosis. The important variable that has a significant role in the economic burden of endometriosis is the recurring nature of this condition, even up to 40-45%. I selected online articles using PRISMA and obtained 122 articles, 4 articles being deleted because of no full text, 8 articles being deleted because of duplication, 17 articles being deleted because of the age of articles more than 10 years, 80 articles being deleted because of not fully relevant with main topics, 4 articles being deleted because of the burden not specific in the economic aspect, and 9 articles are the most perfect choice related with the main topics. In conclusion, endometriosis is a chronic disease experienced by women mostly of productive age, which affects the quality of life, fertility, and even direct economic burdens in the form of recurring and long-term health expenses as well as indirect economic burdens in the form of productivity, many absences from work, and excessive leave. Often due to the treatment process. Based on several journals with similar discussions show significant results in the influence of endometriosis on economic burden.   .